Dynamism the values that drive innovation, job satisfaction, and economic growth - Phelps, Edmund S. (Harvard University Press, 2020)
Nobel Laureate Edmund Phelps argues that the high level of innovation in the West was not a result of scientific discoveries plus entrepreneurship. Rather, modern values--particularly the individualism and self-expression prevailing among the people--fueled the dynamism needed for widespread innovation.